Hypovitaminosis D is associated with depression and anxiety in schizophrenia: Results from the national FACE-SZ cohort. (December 2018) - Fond, G; Godin, O; Schürhoff, F; Berna, F; Bulzacka, E; Andrianarisoa, M; Brunel, L; Aouizerate, B; Capdevielle, D; Chereau, I; Coulon, N; D'Amato, T; et al.
Highlights: Beyond its role in bone metabolism, vitamin D has been shown to have multiple functions including a role in depression and cognitive impairment in general population. Vitamin D has been associated with increased risk of schizophrenia onset, but its role in illness characteristics remains unclear. In this study, vitamin D has been found to be frequent in a national sample of outpatients with schizophrenia, and associated with anxiety and depression. Vitamin D supplementation has been associated with lower rates of anxiety and depression but remains insufficiently prescribed. Abstract: Objective: Hypovitaminosis D has been associated with respectively major depressive disorder, schizophrenia (SZ) and cognitive disorders in the general population, and with positive and negative symptoms and metabolic syndrome in schizophrenia. The objectives were (i) to determine the prevalence of hypovitaminosis D and associated factors (with a focus on depression and cognition) in a national non-selected multicentric sample of community-dwelling SZ subjects (ii) to determine the rate of SZ patients being administered vitamin D supplementation and associated factors. Methods: A comprehensive 2 daylong clinical and neuropsychological battery was administered in 140 SZ subjects included between 2015 and 2017 in the national FondaMental Expert Center (FACE-SZ) Cohort. Hypovitaminosis D was defined by blood vitamin D level <25 nM. Depressive symptoms were assessed by the Positive and Negative Syndrome Scale depressive subscore and current anxiety disorder by the Structured Clinical Interview for Mental Disorders. Results: Hypovitaminosis D has been found in 21.4% of the subjects and none of them had received vitamin D supplementation in the previous 12 months. In multivariate analysis, hypovitaminosis D has been significantly associated with respectively higher depressive symptoms (aOR = 1.18 [1.03–1.35], p = 0.02) and current anxiety disorder (aOR = 6.18 [2.15–17.75], p = 0.001), independently of age and gender. No association of hypovitaminosis D with respectively positive and negative symptoms, cognitive scores or other biological variables has been found (all p > 0.05), however, a trend toward significance has been found for metabolic syndrome ( p = 0.06). Vitamin D supplementation has been administered during the previous 12 months in only 8.5% of the subjects but was associated with lower depressive symptoms (aOR = 0.67 [0.46–0.98], p = 0.04) and lower rate of current anxiety disorder (aOR = 0.06 [0.01–0.66], p = 0.02) compared to patients with hypovitaminosis D. Conclusion: Hypovitaminosis D is frequent and associated with depressive symptoms and anxiety disorders in schizophrenia. Vitamin D supplementation is associated with lower depressive and anxiety symptoms, however patients with hypovitaminosis D remain insufficiently treated.